Lobular capillary haemangioma arising from a vascular malformation - Udhayini, K. V.; Srinivasan, Shreya; Danny, Celestin Geo; Manoharan, D. (International Journal of Research in Dermatology, 2021)
Lobular capillary haemangioma also known as granuloma pyogenicum or pyogenic granuloma, refers to a common, acquired, benign, vascular tumor that arises in tissues such as the skin and mucous membranes. The occasional eruption of a lobular capillary haemangioma from vascular lesions like haemangiomas or existing port-wine stains suggests abnormalities in blood flow.